Deteksi Kelainan Jantung Premature Atrial Contractions (PACS) Berbasis Kombinasi Baseline Wander dan Denoising Menggunakan PR Interval - Iman Fahruzi (JURNAL INTEGRASI, 2012)
Biomedical signals such as heart signals periodically always changing frequencies over time, causing a wave of complexity and heterogeneity. Electrocardiogram (ECG), which is a picture of the heart's electrical potential activity is one of the medical tools that are widely used to make the diagnosis of heart abnormalities. In this study developed an algorithm to detect cardiac abnormalities premature based on the characteristics of ECG signal form the subject of study heart defect Atrial premature contractions (PACs). Testing is done using some data from the MIT-BIH Arrhythmia Database representing some heart abnormalities PACs. The level of accuracy when testing for R peak detection of 99.30% . While the accuracy of detection of heart abnormalities PACs when testing is 93.74%.